2020
DOI: 10.1021/acs.langmuir.0c00152
|View full text |Cite
|
Sign up to set email alerts
|

Highly Correlated Size and Composition of Pt/Au Alloy Nanoparticles via Magnetron Sputtering onto Liquid

Abstract: Pt/Au alloy nanoparticles (NPs) in a wide composition range have been synthesized by room-temperature simultaneous sputter deposition from two independent magnetron sources onto liquid PEG (MW = 600). The prepared NPs were alloyed with the face-centered cubic (fcc) structure. In addition, the particle sizes, composition, and shape are strongly correlated but can be tailored by an appropriate variation of the sputtering parameters. No individual particle but large agglomerates with partial alloy structure forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(54 citation statements)
references
References 61 publications
4
50
0
Order By: Relevance
“…In this context, magnetron sputtering offers exciting new opportunities for the manufacture of novel catalytic materials with controlled sizes and shapes of metal nanoclusters on a variety of supports [14][15][16][17][18] . Crucially, this approach generates highly active clean surfaces, since no chemical stabilisers and/or solvents are involved in the process 16,19 .…”
mentioning
confidence: 99%
“…In this context, magnetron sputtering offers exciting new opportunities for the manufacture of novel catalytic materials with controlled sizes and shapes of metal nanoclusters on a variety of supports [14][15][16][17][18] . Crucially, this approach generates highly active clean surfaces, since no chemical stabilisers and/or solvents are involved in the process 16,19 .…”
mentioning
confidence: 99%
“…While this is not useful if wanting to study small differences between particle sizes in different liquids, the heating effect did help to produce larger particles which were not significantly larger than those produced by others. 11 , 20 , 21 However, more control of the temperature with a heating stage would be preferable for a more constant temperature.…”
Section: Resultsmentioning
confidence: 99%
“…There was additional growth postsputtering after a week or two; however, the Pt nanoparticles were stable for months, indicating that PEG is a good stabilizer and liquid substrate for the production of Pt nanoparticles. The same group has also sputtered Au and PtAu alloys 21 and found that pure Au nanoparticles agglomerate in PEG, so metal–liquid interactions inside the liquid or on the surface are important for stability.…”
Section: Introductionmentioning
confidence: 99%
“…4,15,25,26 The studies in this field reveal important roles of the liquid matrix in the growth behavior, size control, and colloidal stability of the sputtered nanoparticles. [1][2][3][4][5][6][13][14][15][16][17][18][19][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Evaluating the impact of the physicochemical properties of the liquids on the particle size helped understand the particle formation. 6,18,19,[27][28][29][30][31][32][33][34][35][36][37][38] For example, when Au was sputtered onto ionic liquids, the particle nucleation could o...…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, sputtering of Au, Ag, and/or their alloys onto pure liquid PEG, which weakly binds to the particles, often resulted in big agglomerates, aggregations, and precipitates after a week to several months of storage. 6,37,39 Thus, choosing a liquid matrix for sputtering is important for achieving desired particle formation and size and good dispersion stability.…”
Section: Introductionmentioning
confidence: 99%